Activatable near-infrared probes for the detection of specific populations of tumour-infiltrating leukocytes in vivo and in urine - He, Shasha (2023)
Tracking the immune microenvironment of tumours is essential for understanding the mechanisms behind the effectiveness of cancer immunotherapies. Molecular imaging of tumour-infiltrating leukocytes (TILs) can be used to non-invasively monitor the tumour immune microenvironment, but current imaging agents do not distinguish TILs from leukocytes resident in other tissues. Here we report a library of activatable molecular probes for the imaging, via near-infrared fluorescence, of specific TILs (including M1 macrophages, cytotoxic T lymphocytes and neutrophils) in vivo in real time and also via excreted urine, owing to the probes' renal clearance. The fluorescence of the probes is activated only in the presence of both tumour and leukocyte biomarkers, which allows for the imaging of populations of specific TILs in mouse models of cancers with sensitivities and specificities similar to those achieved via flow-cytometric analyses of biopsied tumour tissues. We also show that the probes enable the non-invasive evaluation of the immunogenicity of different tumours, the dynamic monitoring of responses to immunotherapies and the accurate prediction of tumour growth under various treatments.